DIE GEALLIEERDE BESTETTING VAN MADAGASKAR MET SPESIFIEKE VERWYSING NA DIE ROL VAN DIE UNIEVERDEDIGINGSMAG IN DIE OPERASIES (DEEL1) - Grobler, J.E.H. (Scientia Militaria - South African Journal of Military Studies, 2012)
Japan's entry to the Second World War in December 1941.and tha startling success of her forces in South East Asia and the Indian Ocean suddenly increased the strategic importance of the Vichy-held French colony of Madagascar. The island's position in relation to the vital British shipping routes around the Cape had already led to half-hearted diplomatic efforts to secure the neutralisation of Madagascar in 1941. British planners now considered that action was imperative, for they felt that Japan's occupation of the island was merely a question of time. Accordingly in December 1941, Major General Sturges was appointed to command an expeditionary force to seile the island's important harbour at Diego Suarez. The decision to attack Diego Suarez was taken in March 1942 and plans were finalised in great haste. In the initial stages of the Madagascar campaign South Africa provided vital aerial reconnaissance and support and also the intermediate base for the mounting of Britain's first amphibious operation in the Second World War. Important co-ordinating work was done by the Command Staff lit Durban. On 25 April the British expeditionary force began to leave Durban. On 5 May the landings at Diego Suarez began, accompanied by aerial and naval bombardment and by decou attacks elsewhere' along the coast. The beachheads were secured with little trouble but severe opposition was encountered in the Antsirana isthmus where the French resisted fiercely from well-prepared positions. Nevertheless on 8 May the capitulation of the French forces in the Diego Suarez area had been negotiated and the first phase of the Madagascar' operations had been successfully concluded at the cost of relatively few casualties.